The Role of Religion in Society According to Malik Bennabi - Muhammad Yusuf Patria (University of Darussalam Gontor, Indonesia, 2021)
The purpose of this article is to discuss Malik Bennabi's thoughts on the role of religion in society. The discussion was carried out by using the content analysis method for some of Bennabi's works as primary sources and several other relevant references to describe his thoughts. After describing Bennabi's intellectual journey briefly, This paper begins the discussion with his thoughts on the origin of society and its definitions and the basic elements that make up it, namely the Human Realm, The Realm of Thought, and the Realm of Matter. The next discussion is about religion which is a source of moral value for society and encourages society to carry out its historical movements. Based on this, Bennabi concluded that religion is a fundamental factor in the development of society towards civilization and vice versa. Besides, he also believes that every civilization achieved by society has its roots in religious teachings.